OCR BASED PLAYER JERSEY NUMBER IDENTIFICATION FOR GENERATING COMMENTARY FROM VIDEO - M, Prathibha; Anees, Sheena (IJRDO -Journal of Computer Science Engineering, 2015)
Commentary is the explication of aparticular game or an event. In cricket, thecommentary plays an important role in entertainingthe viewers. Without commentary the game won’tbe much effective. The system proposes a solutionwhich is an AI based approach that generates playby-playcommentary and automated colorcommentary from any video clip given, byextracting different features. For generating colorcommentary the most important feature is theplayer identification using the jersey numbers.Using Optical Character Recognition and with thehelp of pattern matching algorithm the numbers areidentified. The methodologies used for the systemare video processing, Human detection, Playeridentification and jersey number identification,Construction of stories related to game and players,matching the identified player with the storyconstructed, and finally generating commentary.